Strategi Pendampingan dan Pembinaan Warga Gereja bagi Generasi Milenial melalui Media Sosial Terhadap Eksistensi Gereja - Kenanya Euodia Ambesa; Yunias Gracia (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: In the modern era, churches face the challenge of rapid societal and technological changes that significantly influence the development and engagement of church members, especially millennials. As the future of families, the church, and the nation, the millennial generation requires targeted spiritual support. Objective: This study aims to identify effective strategies for mentoring and fostering church members from the millennial generation through social media as a means to strengthen the existence and relevance of the church. Method: The research employed a library research method and was conducted in 2022. Data sources included both primary and secondary materials obtained through literature reviews and documentation. The data analysis process involved four stages: (1) data collection; (2) data reduction; (3) data display; and (4) conclusion drawing or verification. Result: The findings indicate that the church serves as a vital institution for the spiritual growth of its members. To remain relevant, the church must become a role model, offering not only spiritual guidance but also contributing positively to society. Utilizing social media platforms proves to be an effective strategy in reaching and mentoring millennial members, thereby reinforcing the church’s role and existence. Conclusion: The use of social media as a tool for mentoring and fostering the millennial generation plays a significant role in maintaining and enhancing the church’s relevance in contemporary society. Contribution: This study offers valuable insights for church leaders and practitioners on the strategic use of digital platforms to engage millennials, ensuring the sustainability and continued influence of the church in a rapidly evolving world.